Optimization and Photostability Studies of Luminescent Organic Dyes for Solar Devices - GILLIGAN, SARAH; McCormack, Sarah J.; Ahmed, Hind; Chandra, Subhash (My University, 2018)
The overall efficiency of a solar cell is limited due to high energy photons within the UV region not being used efficiently. Luminescent Down-Shifting (LDS) layers are used to convert the high energy photons to a lower energy before it reaches the solar cell. The layers are placed on top of the cell and the resulting converted solar spectrum is more efficiently absorbed. In this study, the optimization of organic dyes for LDS thin films is discussed along with the results of photostability tests performed on the layers. The layers comprise combination of BASF Lumogen Yellow 083, Lumogen Orange 240, and Lumogen Violet 570 encapsulated in a polymethyl methacrylate (PMMA) polymer. It observed from the tests conducted over 3 months that the LDS thin-films experienced a degradation. A significant reduction in absorbance and emission spectra was observed. Reductions reached as high as 82% in the integrated spectra.
PVSAT-14
Keywords: Luminescent Down-Shifting; Lumogen; Photostability; Smart & Sustainable Planet; Luminescent Down-Shifting; Lumogen; Organic Dyes